Perancangan Aplikasi E-Lapor Berbasis Android untuk Membantu Komunitas Peduli Sungai Opak Gajah Wong Melakukan Monitoring Potensi Bencana - Agung Yulianto Nugroho; Johan Danu Prasetya; Yohana Noradika Maharani; Tedy Agung Cahyadi; Ficky Adi Kurniawan (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2024)
Information technology has emerged to make various activities easier. One of the important roles of information technology is in providing disaster information. River Care Communities (KPS) which are currently spread across several regions in Indonesia, one of which is River Care Communities Opak Gajah Wong. River Care Communities have an important role in helping reduce disaster risks along river flows. There are various kinds of events that have the potential to cause disasters along river flows, including accumulation of rubbish, landslides on river walls, narrowing and shallowing of rivers, rising water discharge above normal limits and the growth of wild plants that can obstruct river flow. Currently the River Care Community only reports its activities conventionally and has not maximized the existence of information technology. With this conventional method, the delivery of incident reports along the river which is their area of ​​activity is often late, the coordinates are inaccurate and confusing because they are not accompanied by visual images. The conventional pattern of submitting reports means that these reports are too late to be followed up by the relevant agencies and are often simply overlooked. To answer the problems mentioned above, the author conducted research by developing an E-Report application based on Android mobile application using the prototyping method. Currently, there are already several similar complaint applications, but they are not specific to problems that exist along the river flow. The form of complaints and reports in river basins has unique characteristics, where the reporter must enter certain values ​​to determine the level of urgency of the report. With this application, it is hoped that every report from River Care Communities Opak Gajah Wong can be conveyed in real time and immediately receive follow-up from the relevant agencies.